561 Presentation of Rarely Seen Gastrointestinal Telangiectasia in a 4 Year Old Child with Rare Condition Glanzmann'S Thrombasthenia. (October 2012) - Silwal, A; Richards, M
Abstract : A 4 year old girl diagnosed with Glanzmann's Thrombasthenia at the age of 5 months had been admitted on previous occasions to hospital with epistaxis. This encounter describes her presentation with first episode of haematemesis. No focal bleeding source was noted on ENT examination. Emergency endoscopy showed discrete telangiectasia in stomach. The combination of GI telangiectasia and Glanzmann's Thrombasthenia has been rarely reported.